2017
DOI: 10.1136/bmjopen-2016-015241
|View full text |Cite
|
Sign up to set email alerts
|

Association between gender and short-term outcome in patients with ST elevation myocardial infraction participating in the international, prospective, randomised Administration of Ticagrelor in the catheterisation Laboratory or in the Ambulance for New ST elevation myocardial Infarction to open the Coronary artery (ATLANTIC) trial: a prespecified analysis

Abstract: ObjectivesTo evaluate gender differences in outcomes in patents with ST-segment elevation myocardial infarction (STEMI) planned for primary percutaneous coronary intervention (PPCI).SettingsA prespecified gender analysis of the multicentre, randomised, double-blind Administration of Ticagrelor in the catheterisation Laboratory or in the Ambulance for New ST elevation myocardial Infarction to open the Coronary artery.ParticipantsBetween September 2011 and October 2013, 1862 patients with STEMI and symptom durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 38 publications
(29 reference statements)
0
29
0
2
Order By: Relevance
“…There have been several studies demonstrating gender differences in in-hospital outcomes in patients undergoing PCI. Although some studies have reported higher event rates in women than in men, [613] several studies have failed to show gender differences because gender differences in in-hospital outcomes decreased or disappeared after adjustment for age, comorbidity, treatment, and procedure. [1420] Our study also demonstrated that in unadjusted analyses, the risk of in-hospital mortality in women disappeared after controlling for baseline differences in age, comorbidities, disease severity, and angiographic and procedural characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been several studies demonstrating gender differences in in-hospital outcomes in patients undergoing PCI. Although some studies have reported higher event rates in women than in men, [613] several studies have failed to show gender differences because gender differences in in-hospital outcomes decreased or disappeared after adjustment for age, comorbidity, treatment, and procedure. [1420] Our study also demonstrated that in unadjusted analyses, the risk of in-hospital mortality in women disappeared after controlling for baseline differences in age, comorbidities, disease severity, and angiographic and procedural characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are several recent investigations on gender issue in the DES era, their study populations were restricted to patients with acute coronary syndrome, and their results are still conflicting. [12,13,19,20] Therefore, results of our study may deserve clinical attention, because we used the recent database of PCI registry reflecting the current practice of interventional cardiology among unselected patients with CAD. In addition, most of the previous studies were performed in Western countries, [613,1520] and the gender issue on PCI outcome among Asian patients remained to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that gender differencis definitely associated with mortality [15], and such diseases as atherosclerosis that occurs in men early enough (at about 30 years of age), and in women only after menopause. In this case, it is believed that female sex hormones, primarily estrogens, play a key role in antiatherosclerotic protection [12].…”
Section: The Results and Discussionmentioning
confidence: 99%
“…При этом отсутствовали различия в частоте геморрагических осложнений между группами пациентов, получавших антиагрегант на догоспитальном или госпитальном этапах. Не было отмечено гендерных различий при анализе эффективности и безопасности догоспитального назначения тикагрелора [18]. Недавно опубликованы результаты дополнительного анализа исследования ATLANTIC, касающегося преимущества догоспитального назначения тикагрелора у пожилых больных (старше 75 лет) [19].…”
Section: тикагрелорunclassified